2021
DOI: 10.1002/chem.202101471
|View full text |Cite
|
Sign up to set email alerts
|

Coinage Metal Complexes with Di‐tertiary‐butyl Sulfide as Precursors with Ultra‐Low Decomposition Temperature

Abstract: We report here the synthesis of [Cu 2 (TFA) 4 ( t Bu 2 S) 2 ] (1), [Ag 4 (TFA) 4 ( t Bu 2 S) 4 ] (2) and [AuCl( t Bu 2 S)] (3) (TFA = trifluoroacetate), which decompose in solution medium at ultra-low temperature (e. g., in boiling toluene) to afford phase-pure and highly crystalline Cu 9 S 5 , Ag 2 S and metallic Au nanoparticles, respectively. The low decomposition temperature of these precursors is attributed to the facile decomposition mechanism in the di-tertiary-butyl sulfide ligand. These results are a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…As compared to corresponding homoleptic tin(IV) alkylthiolates, which could not be successfully applied in the CVD process, the heteroleptic configuration of 1 and the resulting increase in the Sn-S bond strength ensures a predictable decomposition pattern for it. So while the tertiarybutyl thiolate ligand decomposes in a neat and clean manner due to the presence of an inherent decomposition mechanism [66], the monoanionic tridentate chelate ligand departs in a clean manner without changing the electronic structure of the Sn(II) center or contaminating the growing SnS film, for example, through probable incorporation of heteroatoms (N, O). This, along with the low precursor temperature, enables deposition of high-quality SnS thin films by CVD under mild conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As compared to corresponding homoleptic tin(IV) alkylthiolates, which could not be successfully applied in the CVD process, the heteroleptic configuration of 1 and the resulting increase in the Sn-S bond strength ensures a predictable decomposition pattern for it. So while the tertiarybutyl thiolate ligand decomposes in a neat and clean manner due to the presence of an inherent decomposition mechanism [66], the monoanionic tridentate chelate ligand departs in a clean manner without changing the electronic structure of the Sn(II) center or contaminating the growing SnS film, for example, through probable incorporation of heteroatoms (N, O). This, along with the low precursor temperature, enables deposition of high-quality SnS thin films by CVD under mild conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work indicates that by using non-silylated R 2 E, especially the ones which have facile decomposition mechanism, it should also be possible to prepare a library of precursors that decompose at very low temperature to generate metal chalcogenide nanomaterials under ultra-mild conditions. [43][44][45][46] These studies should be…”
Section: Conclusion and Looking Aheadmentioning
confidence: 99%
“…42 Despite these unique features and high potential, the use of R 2 E in the lowtemperature solution-phase synthesis of metal chalcogenide nanomaterials has received much less attention. Exploiting the facile decomposition mechanism in some of the nonsilylated diorganyl monochalcogenides R 2 E, a recent study from our laboratory has shown (i) the synthesis of metal precursors that decompose at very low temperature to generate metal chalcogenide nanomaterials, 43 and (ii) the direct synthesis of metal chalcogenide NPs at room temperature. [44][45][46][47] In the latter case, the isolation and characterization of the reactive molecular intermediates has helped in understanding the molecule-to-nanoparticle transformation better towards the development of synthetic methods with greater control.…”
Section: Introductionmentioning
confidence: 99%
“…28 Unlike copper selenides, very few reports on the development of SSPs for silver chalcogenide materials can be found in the literature. They include the decomposition of [Ag{SeC 4 H(Me-4,6) 2 N 2 }] 6 • 6MeOH•H 2 O to prepare Ag 2 Se as reported by Sharma et al 25 and the utilization of [Ag 4 (TFA) 4 ( t Bu 2 S) 4 ] for synthesizing the Ag 2 S material by Gahlot et al 29 Previously, we have extensively utilized metal complexes with internally functionalized hemilabile chalcogenolate ligands to afford high quality nanocrystals and thin films which have been evaluated for their photo-responsive behaviour and energy storage applications. [30][31][32] Extending our quest to molecular precursors for coinage metal chalcogenides, in this article, we present the synthesis and characterization of novel air stable copper and silver complexes with 5-methyl-2pyridylselenolate and 4,6-dimethyl-2-pyridylselenolate ligands.…”
Section: Introductionmentioning
confidence: 99%
“…28 Unlike copper selenides, very few reports on the development of SSPs for silver chalcogenide materials can be found in the literature. They include the decomposition of [Ag{SeC 4 H(Me-4,6) 2 N 2 }] 6 ·6MeOH·H 2 O to prepare Ag 2 Se as reported by Sharma et al 25 and the utilization of [Ag 4 (TFA) 4 ( t Bu 2 S) 4 ] for synthesizing the Ag 2 S material by Gahlot et al 29…”
Section: Introductionmentioning
confidence: 99%